UTILIZATION OF ARTIFICIAL AQUIFERS BY ADDING ZEOLITE AND CARBON TO IMPROVE WATER QUALITY - Imamuddin, Mohammad; budiman, budiman; Marsiati, Himmi; Dewi, Firda Rachma; Mahdiani, Nila Sekar (University Muhammadiyah Jakarta, 2025)
Water is the most important component of life. The function of water for living beings cannot be replaced by any other substance. One of the main issues currently faced regarding waterresources is the declining quality of water for both domestic and non-domestic purposes.According to the Regulation of the Minister of Health of the Republic of Indonesia No.492/Menkes/PER/IV/2010 concerning drinking water requirements, it states that safe andhealthy drinking water for consumption must meet requirements that include physical,chemical, and bacteriological criteria. Strict requirements are imposed on drinking waterbecause they are directly related to the biological processes of the body that determine humanquality of life. The consumption rate of drinking water is very high in tropical regions. This isdue to the high humidity, and people in tropical areas require a large amount of drinkingwater to quench their thirst. Therefore, high-quality drinking water is necessary to maintainhealth. The dangers or health risks resulting from the decline in the physical quality of watercan have negative impacts on health. The utilization of groundwater remains a mainstay forcommunities in meeting their domestic and non-domestic water needs. The increasingpopulation has led to a decline in the quality of clean water due to human activities that causeenvironmental pollution. Sources of groundwater pollution include industrial activities, wastedisposal sites, mining areas, residential areas, salt industries, agricultural activities, andlivestock farming.